Ensaios sobre atenção pública à saúde em Minas Gerais - Alessandra Coelho de Oliveira (2007)
The population health status depends on their access to the supplied services and adequacy of the heath care. Taking that into consideration, this dissertation promotes two analyses in order to investigate this accessibility to different levels of health care in the state of Minas Gerais in 2004.The first paper examines the relationship between primary health care and hospitalizations for ambulatory care sensitive conditions. We apply a hierarchical model and Ordinary Least Square by age groups. Results suggest that primary health care provided by municipalities does not affect potentially preventable hospitalization episodes. This result may reflect problems in the quality of the health care service. Supply of hospital beds per capita has a positive effect on the (probability of) hospitalizations for ambulatory care sensitive conditions.The second paper aims to study the access to more complex health care by geographic distribution of services and population. The analysis is based on the flow of patients to use these services at the municipality level. The definition of pole municipalities relies on regional planning and the greatest external demand receivers. We use the biggest direct flow to select pole and the biggest flow based on transitivity criterion as methods to determine the areas (zones) of influence. Serious iniquities for accessibility and disparities at regional planning was found. Our results show in some cases the necessity of huge displacement to utilize more complex services. This happens because of some pole which cannot polarize their planning areas. This is a particular problem since we realize a positive correlation between population with more difficulty to access and the one with worse economic conditions and displacement difficulties.